Management Of Teaching Writing Using Word Processor Computer-Based Program At Muhammadiyah University Of Kendari - Syahriani, Ririn; , Prof. Dr. Bambang Sumardjoko, M.Pd; , Dr. Phil. Dewi Candraningrum, M.Ed (2013)
The objectives of the research are to describe (1) the planning process of teaching writing using word processor computer-based program at Muhammadiyah University of Kendari, (2) the implementation process of teaching writing using word processor computer-based program at Muhammadiyah University of Kendari, and (3) the evaluation process of teaching writing using word processor computer-based program at Muhammadiyah University of Kendari. This is a qualitative research with case study design. This research is conducted at Muhammadiyah University of Kendari. The informants of the research are Head of English Study Program, lecturers of Writing III Course, and students of English Study Program of UMK. The techniques of data collection are through deep interview, observation, and documentation. The techniques of data analysis are by reducing the data, displaying the data, and then drawing conclusions. The data validation is conducted through triangulation of the data. The results of the research show that (1) the planning of teaching writing using word processor computer-based program starts from the arrangement of course outline by the writing course coordinator before the lecturer follows it up with the preparation of infrastructures to conduct the learning. However, the lecturer does not provide the teaching's equipment in RPP that makes the planning of teaching writing III in class C word processor computer-based program is no ideal; (2) Implementation of teaching writing using word processor computer-based program consists of three phases namely opening, core, and close activities, where the techniques of exploration, elaboration, and confirmation have been run very well by the lecturer; and (3) Evaluation conducted by the lecturer in teaching writing using word processor computer-based program is conducted stage by stage for both test and non-test during the class, weekly assignments, and the result of mid and final test. Evaluation has been transparent and fair.